A method for preparing an integrated electrode
Through an integrated electrode preparation method, the porous catalytic reaction layer is used to improve the oxidation reaction capacity of the electrode, which solves the problem of insufficient active functional groups of carbon-based electrode materials, and significantly improves the electrochemical performance of the flow battery.
Patent Information
- Application Number
- CN202411054095.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-08-02
AI Technical Summary
During the high-temperature treatment of existing carbon electrode materials, the number and types of electrode surface active functional groups are insufficient, which affects the electrochemical reaction activity of the interface and limits the performance of the flow battery.
Using an integrated electrode preparation method, a porous catalytic reaction layer is formed by preparing a mixed slurry containing graphene oxide, phenolic resin, epoxy resin and graphene, combined with low- and high-temperature curing, graphitization and oxidation activation, etc. Improve the oxidation reaction capacity of the electrode.
It effectively reduces the interface contact resistance, provides an oxidation reaction site, and significantly improves the electrochemical performance of the flow battery.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrodes, and in particular to a method for preparing an integrated electrode. Background Art
[0002] Electrochemical energy storage is a technology that uses chemical batteries to store electrical energy and release it when needed. Liquid flow batteries have the characteristics of high safety, wide application range, long cycle life, and energy and power density can be designed separately. They are very competitive in the field of electrochemical energy storage and are also the focus of national support in the field of energy storage.
[0003] Redox flow batteries have many advantages over other chemical energy storage batteries, including: long battery life, power and capacity can be freely combined as needed and are independent of each other, and deep discharge will not damage the battery. Redox flow batteries are a new type of chemical reduction energy storage battery that uses metal ions of different valence states in the electrolyte as the positive and negative active substances of the battery. The electrolytes of the positive and negative electrodes are stored separately. The positive and negative electrolytes are pumped into the battery graphite felt by an electric pump to complete the redox reaction, and then flow back to the storage container. From the working principle of redox flow batteries, redox flow batteries have the advantage of large-scale and efficient power storage.
[0004] As one of the key components of liquid flow energy storage batteries, the performance of electrodes has a great impact on liquid flow energy storage batteries. Its conductivity directly affects the ohmic internal resistance of the battery; the affinity between its surface and the electrolyte will affect the transmission rate of active substances at the electrode interface; its electrochemical catalytic activity will also directly determine the intrinsic reaction rate of the electrochemical reaction. In short, the electrode material affects the electrochemical polarization, concentration polarization and ohmic polarization of the battery, involving all components of the battery's electrochemical impedance. These factors greatly affect the working current density and energy efficiency of the battery. The electrode materials widely used in liquid flow batteries are carbon electrodes, including graphite felt, carbon felt, carbon cloth and carbon paper. Such materials have the advantages of high conductivity, good mechanical strength, excellent stability and good corrosion resistance. However, carbon materials are often obtained through high-temperature treatment, resulting in insufficient number and types of active functional groups on the electrode surface, which further affects the electrochemical reaction activity of the interface during use and limits the excellent performance of liquid flow batteries. Summary of the invention
[0005] In view of the shortcomings of the prior art, one of the purposes of the present application is to provide a method for preparing an integrated electrode, which has the advantages of reducing the interfacial contact resistance, and the porous catalytic reaction layer provides a site for oxidation reaction, which can effectively improve the electrochemical performance of the liquid flow battery.
[0006] The above-mentioned purpose of the present application is achieved through the following technical solutions:
[0007] The present application discloses a method for preparing an integrated electrode, comprising the following steps:
[0008] Preparing a mixed slurry: mixing graphene oxide slurry, phenolic resin, epoxy resin, graphene, and anhydrous ethanol in a ratio of (10-30): (20-40): (20-40): (5-10): (20-40) into a mixed slurry having a viscosity of 5000-20000 Pa·s by stirring or acoustic dispersion;
[0009] Soaking: Take a carbon felt with a thickness of 1-5mm and set aside. Press / immerse part of the carbon felt into the mold with the mixed slurry. Do not immerse all the felt, and keep 50-80% of the felt unimmersed.
[0010] Low temperature curing: put the mold into a blast drying oven and dry it at a temperature of 20-60℃ for 20-120min to allow the solvent in the mixed slurry to evaporate slowly. On the one hand, the viscosity of the mixed slurry is increased so that it is closely combined with the carbon fiber. In addition, there is a concentration gradient of the mixed slurry in the vertical direction of the carbon felt surface.
[0011] High temperature curing: Place the mold flatly into a flat vulcanizer, and tightly combine the carbon felt and the mixed slurry under the conditions of a pressure of 0.5-5MPa and a temperature of 150-300°C. The curing time is 2-6 hours.
[0012] High temperature graphitization: The obtained integrated composite electrode is treated in a vacuum graphite furnace at 2300-2800°C for 2-4 hours.
[0013] Oxidation activation: The integrated composite electrode after high-temperature graphitization is treated with high-temperature steam at 400-600°C for 1-3 hours, and the carbon felt part pressed into the mixed slurry is oxidized to increase the oxygen-containing functional groups and improve the redox reaction ability. Note that the hard conductive layer of the integrated composite electrode is directed downward during the oxidation activation process.
[0014] The electrode prepared by the above technical solution has the advantages of reducing the interface contact resistance, and the porous catalytic reaction layer provides an oxidation reaction site, which can effectively improve the electrochemical performance of the liquid flow battery. DETAILED DESCRIPTION
[0015] A method for preparing an integrated electrode according to the present invention comprises the following steps:
[0016] Preparing a mixed slurry: mixing graphene oxide slurry, phenolic resin, epoxy resin, graphene, and anhydrous ethanol in a ratio of (10-30): (20-40): (20-40): (5-10): (20-40) into a mixed slurry having a viscosity of 5000-20000 Pa·s by stirring or acoustic dispersion;
[0017] Soaking: Take a carbon felt with a thickness of 1-5mm and set aside. Press / immerse part of the carbon felt into a mold with mixed slurry (the mold can accommodate the slurry and carbon felt, and can satisfy that the solvent in the slurry can evaporate from the mold when heated, for example, the mold can be a box-shaped body with a flat bottom surface and no cover). Do not immerse all the felt, and keep 50-80% of the felt unimmersed;
[0018] Low temperature curing: put the mold into a blast drying oven and dry it at a temperature of 20-60℃ for 20-120min to allow the solvent in the mixed slurry to evaporate slowly. On the one hand, the viscosity of the mixed slurry is increased so that it is closely combined with the carbon fiber. In addition, there is a concentration gradient of the mixed slurry in the vertical direction of the carbon felt surface.
[0019] High temperature curing: Place the mold flatly into a flat vulcanizer, and tightly combine the carbon felt and the mixed slurry under the conditions of a pressure of 0.5-5MPa and a temperature of 150-300°C. The curing time is 2-6 hours.
[0020] High temperature graphitization: The obtained integrated composite electrode is treated in a vacuum graphite furnace at 2300-2800°C for 2-4 hours.
[0021] Oxidation activation: The integrated composite electrode after high-temperature graphitization is treated with high-temperature steam at 400-600°C for 1-3 hours, and the carbon felt part pressed into the mixed slurry is oxidized to increase the oxygen-containing functional groups and improve the redox reaction ability. Note that the hard conductive layer of the integrated composite electrode is directed downward during the oxidation activation process.
[0022] Example 1
[0023] Preparing a mixed slurry: mixing graphene oxide slurry, phenolic resin, epoxy resin, graphene, and anhydrous ethanol in a ratio of 10:30:30:5:25 into a mixed slurry having a viscosity of 10000 Pa·s by stirring or ultrasonic dispersion;
[0024] Soaking: Take 2mm thick carbon felt for use, press / immerse part of the carbon felt into the mold with the mixed slurry, do not immerse the whole felt, and keep 50% of the felt unimmersed by calculation;
[0025] Low temperature curing: put the mold into a blast drying oven and dry it at 50°C for 60 minutes to allow the solvent in the mixed slurry to evaporate slowly. On the one hand, the viscosity of the mixed slurry is increased so that it is closely combined with the carbon fiber. In addition, there is a concentration gradient of the mixed slurry in the vertical direction of the carbon felt surface.
[0026] High temperature curing: Place the mold flatly into a flat vulcanizer, and under the conditions of a pressure of 2MPa and a temperature of 180°C, tightly combine the carbon felt and the mixed slurry. The curing time is 3 hours.
[0027] High temperature graphitization: The obtained integrated composite electrode is treated in a vacuum graphite furnace at 2300°C for 2 hours.
[0028] Oxidation activation: The integrated composite electrode after high-temperature graphitization is treated with high-temperature steam at 400°C for 1 hour, and the carbon felt part pressed into the mixed slurry is oxidized to increase the oxygen-containing functional groups and improve the redox reaction ability. Note that the hard conductive layer of the integrated composite electrode is directed downward during the oxidation activation process.
[0029] The contact resistance of the electrode prepared by the above technical solution is 2.5 mΩ·cm 2
[0030] Example 2
[0031] A method for preparing an integrated electrode according to the present invention comprises the following steps:
[0032] Preparing a mixed slurry: mixing graphene oxide slurry, phenolic resin, epoxy resin, graphene, and anhydrous ethanol in a ratio of 20:25:25:10:20 by stirring or acoustic dispersion to form a mixed slurry with a viscosity of 15000 Pa·s;
[0033] Soaking: Take 3mm thick carbon felt for use, press / immerse part of the carbon felt into the mold with the mixed slurry, do not immerse the whole felt, and keep 70% of the felt unimmersed by calculation;
[0034] Low temperature curing: put the mold into a blast drying oven and dry it at 40°C for 100 minutes to allow the solvent in the mixed slurry to evaporate slowly. On the one hand, the viscosity of the mixed slurry is increased so that it is closely combined with the carbon fiber. In addition, there is a concentration gradient of the mixed slurry in the vertical direction of the carbon felt surface.
[0035] High temperature curing: Place the mold flatly into a flat vulcanizer, and under the conditions of a pressure of 2.5 MPa and a temperature of 220°C, tightly combine the carbon felt and the mixed slurry. The curing time is 3.5 hours.
[0036] High temperature graphitization: The obtained integrated composite electrode is treated in a vacuum graphite furnace at 2500°C for 2.5 hours.
[0037] Oxidation activation: The integrated composite electrode after high-temperature graphitization is treated with high-temperature steam at 500°C for 1.5 hours, and the carbon felt part pressed into the mixed slurry is oxidized to increase the oxygen-containing functional groups and improve the redox reaction ability. Note that the hard conductive layer of the integrated composite electrode is directed downward during the oxidation activation process.
[0038] The contact resistance of the electrode prepared by the above technical solution is 2.2 mΩ·cm 2
[0039] Example 3
[0040] A method for preparing an integrated electrode according to the present invention comprises the following steps:
[0041] Preparing a mixed slurry: mixing graphene oxide slurry, phenolic resin, epoxy resin, graphene, and anhydrous ethanol in a ratio of 20:20:20:10:30 into a mixed slurry with a viscosity of 5000 Pa·s by stirring or acoustic dispersion;
[0042] Soaking: Take a 4mm thick carbon felt and set aside. Press / immerse part of the carbon felt into the mold with the mixed slurry. Do not immerse all the felt. Keep 80% of the felt unimmersed by calculation.
[0043] Low temperature curing: put the mold into a blast drying oven and dry it at 60°C for 120 minutes to allow the solvent in the mixed slurry to evaporate slowly. On the one hand, the viscosity of the mixed slurry is increased so that it is closely combined with the carbon fiber. In addition, there is a concentration gradient of the mixed slurry in the vertical direction of the carbon felt surface.
[0044] High temperature curing: Place the mold flatly into a flat vulcanizer, and under the conditions of a pressure of 4MPa and a temperature of 260°C, tightly combine the carbon felt and the mixed slurry. The curing time is 4 hours.
[0045] High temperature graphitization: The obtained integrated composite electrode was treated in a vacuum graphite furnace at 2650°C for 3 hours.
[0046] Oxidation activation: The integrated composite electrode after high-temperature graphitization is treated with high-temperature steam at 600°C for 2.5 hours, and the carbon felt part pressed into the mixed slurry is oxidized to increase the oxygen-containing functional groups and improve the redox reaction ability. Note that the hard conductive layer of the integrated composite electrode is directed downward during the oxidation activation process.
[0047] The contact resistance of the electrode prepared by the above technical solution is 2.6 mΩ·cm 2
[0048] Example 4
[0049] A method for preparing an integrated electrode according to the present invention comprises the following steps:
[0050] Preparing a mixed slurry: mixing graphene oxide slurry, phenolic resin, epoxy resin, graphene, and anhydrous ethanol in a ratio of 30:20:20:10:20 by stirring or acoustic dispersion to form a mixed slurry with a viscosity of 20000 Pa·s;
[0051] Soaking: Take 5mm thick carbon felt for use, press / immerse part of the carbon felt into the mold with the mixed slurry, do not immerse all the felt, and keep 60% of the felt unimmersed by calculation;
[0052] Low temperature curing: put the mold into a blast drying oven and dry it at 45°C for 80 minutes to allow the solvent in the mixed slurry to evaporate slowly. On the one hand, the viscosity of the mixed slurry is increased so that it is closely combined with the carbon fiber. In addition, there is a concentration gradient of the mixed slurry in the vertical direction of the carbon felt surface.
[0053] High temperature curing: Place the mold flatly into a flat vulcanizer, and tightly combine the carbon felt and the mixed slurry under the conditions of a pressure of 5 MPa and a temperature of 300°C. The curing time is 5 hours.
[0054] High temperature graphitization: The obtained integrated composite electrode was treated in a vacuum graphite furnace at 2700°C for 3.5 hours.
[0055] Oxidation activation: The integrated composite electrode after high-temperature graphitization is treated with high-temperature steam at 550°C for 1.5 hours, and the carbon felt part pressed into the mixed slurry is oxidized to increase the oxygen-containing functional groups and improve the redox reaction ability. Note that the hard conductive layer of the integrated composite electrode is directed downward during the oxidation activation process.
[0056] The contact resistance of the electrode prepared by the above technical solution is 2.2 mΩ·cm 2
[0057] Comparative Example 1
[0058] A method for preparing an integrated electrode according to the present invention comprises the following steps:
[0059] Preparing a mixed slurry: mixing graphene oxide slurry, phenolic resin, epoxy resin, graphene, and anhydrous ethanol in a ratio of 10:30:30:5:25 into a mixed slurry with a viscosity of 10000 Pa·s by stirring or acoustic dispersion;
[0060] Soaking: Take 2mm thick carbon felt for use, press / immerse part of the carbon felt into the mold with the mixed slurry, do not immerse the whole felt, and keep 60% of the felt unimmersed by calculation;
[0061] Low temperature curing: put the mold into a blast drying oven and dry it at 60°C for 120 minutes to allow the solvent in the mixed slurry to evaporate slowly. On the one hand, the viscosity of the mixed slurry is increased so that it is closely combined with the carbon fiber. In addition, there is a concentration gradient of the mixed slurry in the vertical direction of the carbon felt surface.
[0062] High temperature curing: Place the mold flatly into a flat vulcanizer, and under the conditions of a pressure of 4MPa and a temperature of 280°C, tightly combine the carbon felt and the mixed slurry. The curing time is 4 hours.
[0063] High temperature graphitization: The obtained integrated composite electrode was treated in a vacuum graphite furnace at 2650°C for 3 hours.
[0064] Oxidation activation: The integrated composite electrode after high-temperature graphitization is treated with high-temperature steam at 500°C for 1.5 hours, and the carbon felt part pressed into the mixed slurry is oxidized to increase the oxygen-containing functional groups and improve the redox reaction ability. Note that the hard conductive layer of the integrated composite electrode is directed downward during the oxidation activation process.
[0065] The contact resistance of the electrode prepared by the above technical solution is 1.6 mΩ·cm 2
[0066] Comparative Example 2
[0067] A method for preparing an integrated electrode according to the present invention comprises the following steps:
[0068] Preparing a mixed slurry: mixing graphene oxide slurry, phenolic resin, epoxy resin, graphene, and anhydrous ethanol in a ratio of 30:20:20:10:20 by stirring or acoustic dispersion to form a mixed slurry with a viscosity of 20000 Pa·s;
[0069] Soaking: Take 5mm thick carbon felt for use, press / immerse part of the carbon felt into the mold with the mixed slurry, do not immerse the whole felt, and keep 80% of the felt unimmersed by calculation;
[0070] Low temperature curing: put the mold into a blast drying oven and dry it at 55°C for 80 minutes to allow the solvent in the mixed slurry to evaporate slowly. On the one hand, the viscosity of the mixed slurry is increased so that it is closely combined with the carbon fiber. In addition, there is a concentration gradient of the mixed slurry in the vertical direction of the carbon felt surface.
[0071] High temperature curing: Place the mold flatly into a flat vulcanizer, and under the conditions of a pressure of 4.5 MPa and a temperature of 250°C, tightly combine the carbon felt and the mixed slurry. The curing time is 4 hours.
[0072] High temperature graphitization: The obtained integrated composite electrode was treated in a vacuum graphite furnace at 2700°C for 3.5 hours.
[0073] Oxidation activation: The integrated composite electrode after high-temperature graphitization is treated with high-temperature steam at 550°C for 2.5 hours, and the carbon felt part pressed into the mixed slurry is oxidized to increase the oxygen-containing functional groups and improve the redox reaction ability. Note that the hard conductive layer of the integrated composite electrode is directed downward during the oxidation activation process.
[0074] The contact resistance of the electrode prepared by the above technical solution is 1.6 mΩ·cm 2
[0075] The implementation principle of this embodiment is: the graphene oxide slurry is reduced to graphene to reduce the contact resistance, and the carbon and carbon felt have significantly increased specific surface area and oxygen-containing functional groups after activation, which can improve the electrocatalytic activity of the redox reaction of the liquid flow battery.
[0076] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing an integrated electrode, characterized in that: Preparing a mixed slurry: mixing graphene oxide slurry, phenolic resin, epoxy resin, graphene, and anhydrous ethanol in the proportion of (10-30): (20-40): (20-40): (5-10): (20-40) by stirring or acoustic dispersion to form a mixed slurry with a viscosity of 5000-20000 Pa·s; Soaking: Take a carbon felt with a thickness of 1-5 mm and set aside. Press / immerse part of the carbon felt into the mold with the mixed slurry. Do not immerse all the felt, and keep 50-80% of the felt unimmersed. Low temperature curing: Place the mold in a blast drying oven and dry it at 20-60°C for 20-120 min to allow the solvent in the mixed slurry to evaporate slowly. On the one hand, the viscosity of the mixed slurry is increased so that it is closely combined with the carbon fiber. In addition, there is a concentration gradient of the mixed slurry in the vertical direction of the carbon felt surface. High temperature curing: Place the mold flatly into a flat vulcanizer, and tightly combine the carbon felt and the mixed slurry under the conditions of a pressure of 0.5-5MPa and a temperature of 150-300°C. The curing time is 2-6 hours. High temperature graphitization: The high temperature cured product is treated in a vacuum graphite furnace at 2300-2800 ℃ for 2-4 hours; Oxidation activation: The high-temperature graphitized product is treated with high-temperature steam at 400-600 °C for 1-3 hours, and the carbon felt part pressed into the mixed slurry is oxidized to increase the oxygen-containing functional groups and improve the redox reaction ability. The hard conductive layer of the integrated composite electrode is directed downward during the oxidation activation process.
Citation Information
Patent Citations
Carbon electrode material for manganese / titanium-based redox flow battery
CN113544885A
Integrated gradient porosity electrode material, preparation method thereof and all-vanadium redox flow battery
CN117059828A